Imperative Directives: Orientations to Accountability. Issue 3 (2nd July 2016) - Kent, Alexandra; Kendrick, Kobin H.
ABSTRACT: Our analysis proceeds from the question that if grammar alone is insufficient to identify the action of an imperative (e.g., offering, directing, warning, begging, etc.), how can interlocutors come to recognize the specific action being performed by a given imperative? We argue that imperative directives that occur after the directed action could have first been relevantly performed explicitly to direct the actions of the recipient and tacitly treat the absence of the action as a failure for which the recipient is accountable. The tacit nature of the accountability orientation enables both parties to focus on restoring progressivity to the directed course of action rather than topicalizing a transgression. Data are from everyday interactions in British and American English.